Blended learning effect towards Indonesian education students' learning achievement - Anwar Sewang (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The success of a teacher in delivering a subject matter is not only influenced by his ability (competence of the teacher) in mastering the material to be delivered. But there are other factors that must be mastered so that he is able to convey the material professionally and effectively. In pedagogical competence, one of the points is that a teacher must master learning theory and educational learning principles.Mastery includes the competence of teachers in applying various approaches, strategies, methods, and learning techniques that educate creatively in the subjects they master. Blended learning is one of the strategies in learning process to build up the students' learning achievement.This paper examines the effects of blended learning on FKIP students of Universitas Sulawesi Barat Majene. In this study was selected students and divided into two equal groups; one experimental (blended learning) and one control group (traditional method). This paper uses the experimental methods and data analysis was carried out by using the Statistical Package for Social Science (SPSS) 25 version. The results for the research statistically revealed that the blended learning group significantly did better on the post-test (p<0.5). Therefore, the null hypothesis of the study with blended learning does not have any significant effect on student, in the other name it was rejected and the blended learning appeared to have greater effect on student of FKIP Universitas Sulawesi Barat. it can be claimed that receiving instruction by using blended learning can facilitate to learn.